2023
DOI: 10.3390/ijerph20054290
|View full text |Cite
|
Sign up to set email alerts
|

Current and Future Trends in Driver Behaviour and Traffic Safety Scholarship: An African Research Agenda

Abstract: Road traffic accidents are strongly associated with driver behaviour. Africa, as a region, has the highest road accident fatality rate, but there is very little research dealing with this critical issue on the continent. This paper, therefore, sought to establish the state of driver behaviour and road safety scholarship in Africa to determine current research trends as well as potential future research directions. To this end, two bibliometric analyses were conducted, one which considered the issue from an Afr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…However, in general, the output of research documents on commercial drivers' behaviour is still very low. Most articles within the top sources focus on specialized investigations conducted at the country level and targeting specific aspects which are in accordance with [18]. In light of this outcome, it is suggested that these resources have provided valuable insights that can be utilized by researchers in their future investigations on road user behaviour.…”
Section: Data Sources and Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…However, in general, the output of research documents on commercial drivers' behaviour is still very low. Most articles within the top sources focus on specialized investigations conducted at the country level and targeting specific aspects which are in accordance with [18]. In light of this outcome, it is suggested that these resources have provided valuable insights that can be utilized by researchers in their future investigations on road user behaviour.…”
Section: Data Sources and Search Strategymentioning
confidence: 99%
“…However, despite several research studies on the role of drivers' behaviour on the growing accident rate in Africa [3], [18], [19], [21] metric studies or assessments of research output on commercial drivers'…”
Section: Introductionmentioning
confidence: 99%
“…14 The driver's attitude and behavior are related to sustainable development, and conducting research with such approaches informs policymakers of the need to implement interventions to improve driver behavior and reduce the incidence of accidents with regard to better socioeconomic conditions. 15 An attitude is a way of relating to someone or something, or a way of behaving that is influenced by that feeling or opinion. 16 Medical science students make up a significant portion of the young population of any society.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to adults, younger drivers have a greater chance of being involved in fatal crashes caused by distracted driving 14 . The driver's attitude and behavior are related to sustainable development, and conducting research with such approaches informs policymakers of the need to implement interventions to improve driver behavior and reduce the incidence of accidents with regard to better socioeconomic conditions 15 . An attitude is a way of relating to someone or something, or a way of behaving that is influenced by that feeling or opinion 16 …”
Section: Introductionmentioning
confidence: 99%